Digestive Alkaline Proteases from Zosterisessor ophiocephalus, Raja clavata, and Scorpaena scrofa: Characteristics and Application in Chitin Extraction. (4th September 2011) - Nasri, Rim; Younes, Islem; Lassoued, Imen; Ghorbel, Sofiane; Ghorbel-Bellaaj, Olfa; Nasri, Moncef
Abstract : The aim of this work was to study some biochemical characteristics of crude alkaline protease extracts from the viscera of goby ( Zosterisessor ophiocephalus ), thornback ray ( Raja clavata ), and scorpionfish ( Scorpaena scrofa ), and to investigate their applications in the deproteinization of shrimp wastes. At least four caseinolytic proteases bands were observed in zymogram of each enzyme preparation. The optimum pH for enzymatic extracts activities of Z. ophiocephalus, R. clavata, and S. scrofa were 8.0-9.0, 8.0, and 10.0, respectively. Interestingly, all the enzyme preparations were highly stable over a wide range of pH from 6.0 to 11.0. The optimum temperatures for enzyme activity were 50 ∘ C for Z. ophiocephalus and R. clavata and 55 ∘ C for S. scrofa crude alkaline proteases. Proteolytic enzymes showed high stability towards non-ionic surfactants (5% Tween 20, Tween 80, and Triton X-100). In addition, crude proteases of S. scrofa, R. clavata, and Z. ophiocephalus were found to be highly stable towards oxidizing agents, retaining 100%, 70%, and 66%, respectively, of their initial activity after incubation for 1 h in the presence of 1% sodium perborate. They were, however, highly affected by the anionic surfactant SDS. The crude alkaline proteases were tested for the deproteinization of shrimp waste in the preparation of chitin. All proteases were found to be effective in the deproteinization of shrimp waste. The protein removals after 3 h of hydrolysis at 45 ∘ C with an enzyme/substrate ratio (E/S) of 10 were about 76%, 76%, and 80%, for Z. ophiocephalus, R. clavata, and S. scrofa crude proteases, respectively. These results suggest that enzymatic deproteinization of shrimp wastes by fish endogenous alkaline proteases could be applicable to the chitin production process.